2015
DOI: 10.1590/1980-5497201500060013
|View full text |Cite
|
Sign up to set email alerts
|

Estimativa de pessoas com diagnóstico de câncer no Brasil: dados da Pesquisa Nacional de Saúde, 2013

Abstract: ABSTRACT:Objective: To describe the profile of patients who reported a medical diagnosis of cancer and describe the most prevalent types of cancer, according to selected variables. Methods: A descriptive study that used data from the National Survey of Health, 2013, to estimate prevalence and their values of confidence interval (95%CI). Results: Less than 2% of adults reported a medical diagnosis of cancer, with most reported by women, people over 60, among whites, residents in the village and residents of Sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
23
1
58

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(92 citation statements)
references
References 17 publications
2
23
1
58
Order By: Relevance
“…This perspective can be identified by considering the predominance of advanced age patients undergoing cancer treatment, as evidenced in this study and in similar results described in the literature 11 - 13 .…”
Section: Discussionsupporting
confidence: 81%
“…This perspective can be identified by considering the predominance of advanced age patients undergoing cancer treatment, as evidenced in this study and in similar results described in the literature 11 - 13 .…”
Section: Discussionsupporting
confidence: 81%
“…The most prevalent type of cancer in the study was the breast cancer, which, according to a 2015 study, is the most commonly found in women in Brazil and in the world, and the second most common in the general population 26 . Prostate cancer is the second most prevalent type of cancer in men and the fourth most common type in the world, after bowel cancer, which is the third most common in the world 2 .…”
Section: Discussionmentioning
confidence: 95%
“…Os resultados encontrados nesta pesquisa acompanham o perfil epidemiológico do câncer no Brasil e evidenciam que mais da metade dos pacientes são do sexo feminino. Estudo desenvolvido em município da região sul do Brasil mostrou resultado semelhante (8) . A estimativa de novos casos de câncer para 2016, realizada pelo Instituto Nacional do Câncer (INCA), indicava a ocorrência de 300.870 novos diagnósticos de cânceres em mulheres e 295.200 em homens, demonstrando, assim, uma perspectiva de maior incidência do desenvolvimento de câncer em mulheres quando comparada aos homens(2).…”
Section: Métodounclassified
“…Os tipos de câncer com maior frequência na amostra estudada foram os cânceres de mama, seguidos por próstata, colón/reto e cabeça/pescoço. Estudo desenvolvido na região sul do país evidenciou câncer de mama e próstata como os mais frequentes (8). Sem considerar os tumores de pele não melanoma, o câncer de mama é mundialmente o tipo de câncer mais frequente em mulheres.…”
Section: Métodounclassified